Edukasi Pola Asuh Positif Sebagai Upaya Preventif Bullying pada Remaja di SMA Perintis 1 Bandar Lampung - Rilyani Rilyani; Sumarni Sumarni; Muhammad Fiqi Dwiartho; Putri Yolanda Utama; Neisa Adhani; Mia Putri; Rama Rajasa Ferlanda Alam (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Bullying is a form of violence carried out individually or in groups by peers against someone who is physically weak or infirm with the aim of harming others and obtaining certain benefits or satisfaction. In Indonesia, data from the Indonesian Child Protection Commission (KPAI) shows that there were 369 complaints related to bullying between 2011 and 2014, with 25% of all complaints, or 1,480, coming from the education sector. Parenting patterns prevent actively and significantly engaging in bullying behavior while acting. The aim of this activity is to increase students' knowledge regarding preventing bullying with positive parenting. The results obtained from these four categories were 326 points. The findings from this activity were that all participants participated in the activity well and were able to answer the questions given. Positive parenting patterns carried out by parents will influence adolescent behavior. Family and social support play an important role in influencing bullying